An Analysis of Madrasah Curriculum and Its Implementation in Basic Education Institutions - Putra, Muhammad Irwansah; Neliwati, Neliwati; Azmar, Azmar; Azhar, Azhar (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the curriculum used by madrasas and their implementation in basic education institutions. This study uses a qualitative approach with a descriptive study method. Data collection was carried out using observation techniques, interviews, and document studies. Furthermore, data analysis uses data sorting, presentation, and data verification techniques. The results of this study conclude that the curriculum used by Madrasah Tsanawiyah Al-Washliyah Stabat is the 2013 curriculum (revised) as a learning guide and human resource development (teachers and students) in madrasas. Implementation of the curriculum begins with socialization to teachers regarding changes in the 2013 curriculum, providing training for teachers to improve classroom management skills and the learning process, preparing academic schedules, completing textbooks (for students or teachers according to the latest edition), as well as carrying out academic supervision and managerial in the learning process.